GRAFFITI IN INDIAN ELECTION CAMPAIGNING AND ITS DECLINE - Das, Saday Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Graffiti has been an integral part of political campaigning across the Globe including India for a significant period of time. This paper seeks to explore the role of Graffiti in Indian election campaigning and the reasons behind its decline in recent years. By examining various scholarly resources and analyzing political trends, this research paper delves into the impact of Graffiti on political messaging, public perceptions and the changing dynamics of election campaigning in India.